Bridging Digital Divide in India : Positive Outlook Amid COVID-19 - Indu,; Thadikaran, Greeshma Benny; Chellaswamy, Karthigai Prakasam (Prabandhan: Indian Journal of Management, 2022)
The digital divide is described as the gap in access to, knowledge of, use of, or ability to comprehend information and communication technology (ICT) between different societal groups. The digital divide can often give way to an upsurge in social inequalities. This study intended to comprehend the extent of the rural-urban digital divide in India regarding access to the internet and to analyze the increase or decrease in the same due to the global coronavirus pandemic. The analysis of the paper was primarily based on secondary data collected from the report on â€œThe Indian Telecom Services Performance Indicatorsâ€ issued by the Telecom Regulatory Authority of India for June 2019 and June 2020. Percentage analysis was employed to comprehend the trend of the digital divide in terms of access for the years 2019 and 2020. The results disclosed that there was an increase in internet access in the rural population during the time frame of COVID-19, and this increase has led to a decrease in the digital divide in terms of access to the internet. Moreover, the study revealed that COVID-19, to some extent, has resulted in bridging the rural-urban digital divide in India in terms of access. The study further highlighted the importance of digital literacy and access to ICT, and suggested ways to improve digital literacy in India.